How multimorbidity relates to road traffic accident among older adults and elderly population: insights from longitudinal aging study in India (1st wave) - Halder, Pritam; Seth, Ashwani Kumar; Kansal, Shubham; Pal, Saumyarup; Mamgai, Anshul (International Journal Of Community Medicine And Public Health, 2024)
Background: Multimorbidity and road traffic accidents increase with increasing age. Supplemented with increasing life expectancy at birth, both multimorbidity and RTAs will contribute significantly to the growing disease burden of the country. The objective of the study was to determine the association between multimorbidity and RTAs among older adults (above 45 years) and the elderly (above 60 years) population in India. Methods: A secondary data analysis was conducted using the Longitudinal Ageing Study in India (LASI)-1st wave data (April 2017 to December 2018). Participants having at least two chronic health conditions were described as multimorbidity. Road traffic accidents (RTAs) was taken as the outcome variable. Univariate followed by multivariable logistic regression was conducted between the outcome variable and each explanatory variable. Results: Data extracted consisted of 34704 (51.1%) older adults and 31902 (47.9%) elderly. Multimorbidity was present in 25054 (37.6%) individuals. Among the RTA group, 325 (26.5%) individuals had multimorbidity. The elderly with multimorbidity (at least two) were associated with the RTA with an adjusted odds ratio (CI) of 0.55 (0.45-0.67) and p value of <0.001 in comparison to older adults. Clerical and skilled individuals with multimorbidity were associated with RTA in comparison to unemployed individuals with multimorbidity with an adjusted odds ratio (CI) of 1.40 (1.10-1.79) and p value of 0.007. Conclusions: The RTA was evident among males aged 45-60 years with multimorbidity. Clerical and skilled individuals with multimorbidity were more prone to RTA. These individuals should be encouraged to take necessary measures to promote healthy living and adhere to them.